ИСКУСТВОТО НА ТАJНАТА (Филологические заметки, 2019)
In this text is presented the syntagm «inner philosophy» in the byzantian apprehension, which, in accordance with the author’s opinion, is authentic. Opposite in relation to the tendencies, which proclaim the philosophy as a thinking-technique, in this study is represented the thesis that the byzantian philosophy is based on the experience of faith and on the experience of the secret.